Blockchain-Based Therapeutic Agreement Model For Patient Legal Protection in Telemedicine - Ratih, Ratih Pratiwi Syurkawi; Dodi, Dodi Jaya Wardana; Ifahda, Ifahda Pratama Hapsari; Deni, Deni Setiyawan; Eka, Eka Nurjanah (Jurnal Ius Constituendum, 2026)
This study aims to analyze and formulate an optimized legal protection model for patients in telemedicine services in Indonesia by developing a blockchain-based therapeutic agreement framework that strengthens legal certainty, informed consent, and personal data security. Using a normative juridical method with statutory, conceptual, and comparative approaches, this research examines Indonesia’s Health Law, the Personal Data Protection (PDP) Law, the Electronic Information and Transactions (EIT) Law, and sectoral telemedicine regulations, supported by relevant scholarly literature. The findings demonstrate that Indonesia’s telemedicine governance remains constrained by regulatory gaps and normative disharmony, particularly in direct-to-patient services, due to the absence of standardized electronic informed consent (e-consent) procedures, weak digital identity verification, and unclear demarcation of liability between physicians as medical professionals and platforms as electronic system providers. These weaknesses expose patients to heightened risks of malpractice disputes, evidentiary challenges in electronic medical records, and personal data breaches. To address these issues, this study proposes a blockchain-enabled therapeutic agreement model integrated with smart contract mechanisms to ensure immutable consent records, transparent audit trails, enforceable allocation of rights and obligations, and privacy-by-design compliance with the PDP Law. The novelty of this study lies in integrating health law principles with blockchain-based contractual architecture as a concrete regulatory and operational blueprint for patient protection within Indonesia’s digital health ecosystem. This model provides policy implications for establishing standardized digital contract templates, risk-based supervision, and interoperable verification systems to enhance trust, accountability, and equitable access to telemedicine, including in frontier, outermost, and remote (3T) regions.